2021
DOI: 10.1097/icl.0000000000000788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eye Spray Phospholipid Concentration on the Tear Film and Ocular Comfort

Abstract: Objectives: To evaluate the effect of eye spray phospholipid concentration on symptoms and tear film stability. Methods: High-concentration (Tears Again, Optima Pharma GmbH, Hallbergmoos, Germany) and low-concentration (Ocuvers, Innomedis AG, Germany) phospholipid eye sprays were sprayed onto the closed eyelids of 30 subjects (33.261.8 years; 20 women) in a multicentered, prospective, crossover study. Ocular comfort (visual analog scale) and noninvasive tear film stability (NIBUT) of each eye were evaluated be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Those who have the evaporative dry eye subtype gain more benefit from artificial tears including lipids, as we have found previously 330,331 . Lipid sprays are effective despite being sprayed on the closed eyelid, rather than directly onto the ocular surface, 332 although this does depend on the formulation 333 . These findings provide the evidence that informs our current management of patients with dry eye disease (Fig.…”
Section: Technology-driven Enhancements In Ocular Surface Disease Dia...supporting
confidence: 63%
See 1 more Smart Citation
“…Those who have the evaporative dry eye subtype gain more benefit from artificial tears including lipids, as we have found previously 330,331 . Lipid sprays are effective despite being sprayed on the closed eyelid, rather than directly onto the ocular surface, 332 although this does depend on the formulation 333 . These findings provide the evidence that informs our current management of patients with dry eye disease (Fig.…”
Section: Technology-driven Enhancements In Ocular Surface Disease Dia...supporting
confidence: 63%
“…330,331 Lipid sprays are effective despite being sprayed on the closed eyelid, rather than directly onto the ocular surface, 332 although this does depend on the formulation. 333 These findings provide the evidence that informs our current management of patients with dry eye disease (Fig. 4).…”
Section: Technology-driven Enhancements In Ocular Surface Disease Dia...mentioning
confidence: 69%
“… Perez-Balbuena et al 2016 47 Randomized, double-masked, multi-center study Xanthan gum 0.09% and chondroitin sulfate 0.1% PEG 400 0.4% and PG 0.3% N = 76 N = 72 49.9 ± 16.0 45.5 ± 12.7 2 months (4x/day) None Schirmer’s, TBUT, Symptoms, Corneal & conjunctival staining Schirmer’s, TBUT, Symptoms Corneal & conjunctival staining Clinical Trial NCT01657253 Cochrane Risk of Bias R+C?M+O?I+S+B+ Pinto-Bonilla et 2015 42 Randomized, open-label, crossover, single-center study Trehalose and SH 1.5mg/mL -Thealoz Duo PEG & HP-guar - Systane N = 9 N = 8 45.3 ± 11.8 53.8 ± 14.6 1 week (5x/day) (Actual 3.7±0.9 / 3.5±0.9) None Symptoms, Corneal & conjunctival staining, Schirmer’s, TBUT Symptoms Schirmer’s TBUT, Corneal & conjunctival staining CLINICAL TRIAL NOT REGISTERED Postorino et al 2018 53 Randomized, investigator-masked, single-center study HA crosslinked + CoQ10 HA 0.15% crosslinked N = 20 N = 20 60.2 ± 13.6 60.9 ± 12.5 3 months (4x/day) Symptoms, MGD assessment, corneal / conjunctival staining, epithelial hyperreflectivity and keratocytes with HA + CoQ10 Symptoms, corneal aesthesiometry TBUT OSDI MGD assessment, corneal / conjunctival staining, epithelial hyperreflectivity and keratocytes with HA + CoQ10 only Corneal aesthesiometry TBUT Fluorescein staining only Clinical Trial NCT03074344 - meibomian gland assessment and confocal additionally reported Cochrane Risk of Bias R+C+M-O?I?S-B? Pult et al 2021 77 Randomized, double-masked, crossover, multi-center study Phospholipid 0.98% - Tears Again Phospholipid 0.12% - Ocuvers N=30 (all treatments) 33.2±1.8 …”
Section: Artificial Tears For Dry Eye Diseasementioning
confidence: 99%
“… 75 Higher liposomal concentration increases effectiveness. 76 , 77 Lower osmolarity drops increase the effectiveness of an artificial tear drop. 46 Higher concentration (viscosity) CMC is more effective in reducing corneal and conjunctival staining, but caused more reports of visual disturbance.…”
Section: Artificial Tears For Dry Eye Diseasementioning
confidence: 99%